Reading strategies - from L1 to L2. - Dota, Maria Inez Mateus [UNESP] (Universidade Estadual Paulista (Unesp), 1990)
This paper intends to present a selection of the most useful reading strategies for the typical ESP students in Brazilian universities, showing whether the readers use them in their native language or not, the way the teacher should develop these strategies in the classroom, the problems involved in their use and the reasons for using them.
Keywords: Reading strategies; native language (L1); foreign language (L2); ESP (English for Specific Purposes)